Teaching Quality and Teacher Welfare A Critical Policy Analysis of Government Employees with Work Agreements - Hasan, Suhandi (Business Finance Analyst Co., 2025)
The Government Employees with Work Agreement (PPPK) policy has been introduced to address the shortage of teachers and to enhance the quality of education. This policy is designed to prioritize competence and qualifications, ensuring that teacher recruitment is aligned with the actual requirements in the field. Employing a Critical Policy Analysis (CPA) framework, the study seeks to critically evaluate the impact of the PPPK policy on the quality of teaching and the welfare of teachers in Indonesia. This research scrutinizes three pivotal legal frameworks: Law No. 20 of 2023, which pertains to the State Civil Apparatus; Government Regulation No. 49 of 2018 regarding the management of PPPK; and Ministerial Regulation No. 2 of 2019 regarding PPPK procurement. The study explores how these legal frameworks delineate teaching quality, the structural barriers PPPK teachers face, and the power dynamics among policymakers, local governments, and educators. The findings indicate that the policy is intricately linked to ideological assumptions prioritizing market-oriented accountability and managerial efficiency over the comprehensive needs of educators.